Does Support Price Policy Drive Yield Rate? An Econometric Investigation of Wheat and Sugarcane Crops in Pakistan - Ishaq, Maryam; Nasim, Ismat; Rehman, Atiq ur (Pakistan Journal of Humanities and Social Sciences, 2024)
The governments of developing economies incentivize the cultivators of their most strategic crops by offering them minimum support price for their yield. This study aims at identifying distinctively the short-run dynamics and the long-run causal linkage of support price and yield rates for two major food crops of the country; wheat and sugarcane. Employing advance time-series econometric estimators of Error Correction Model (ECM) and Fully Modified OLS (FMOLS) cointegration regression, results indicate the valid existence of hypothesized relationship over both short and longer time horizons. Each year, the short-term divergence of two crop yields from their long-run equilibrium paths turns out to be corrected with high speed of adjustment. The long-run association between two variables is also found evident with decent magnitude and high degree of statistical significance. These findings favour the use of support prices as a long-term policy tool for encouraging cultivation of wheat and sugarcane crops in country. However, the overall welfare consequences of such a policy should never be over-rated in a society like Pakistan which is largely characterized by horrific levels of corruption and innumerable administrative bottlenecks.